Machine Performance Sustainability Design with Overall Measure of Maintenance Performance (OMMP) and Integrated Environment Performance Measurement System (IEPMS) - Pramudya, Afif Andamari; Husada, Zeplin (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Comprehensive effectiveness analysis of water treatment plant maintenance systems To date, the Integrated Environmental Performance Measuring System (IEPMS) and the Overall Maintenance Performance Measuring Process (OMMP) have become the standards used in evaluating environmental performance, so good integration between these two systems is very important. The purpose of this study is how PT. B, B, C assesses the effectiveness of its maintenance, then how to evaluate the environmental performance of produced water and wastewater. As well as determining the performance indicators of the maintenance of the treatment plant and wastewater of PT. The following research uses descriptive. Based on the results of this study, it concludes that using the OMMP method, PT ABC Offshore has an overall maintenance performance of 5.388, which indicates a high level of maintenance performance. Next is equipment downtime, operating hours, and emergency working hours. Finally, the company's overall environmental performance scored 9.57 by entering the green zone and indicating that PT ABC Offshore met the environmental performance control target for 12 months. Root Cause Analysis (RCA) results show that only 1 KEPI is still in the caution zone and is recommended for improvement.